Assessing Interest and Program Development for a Postgraduate Diploma in General Practice among Medical Officers and General Practitioners in Malaysia - Ganason, Anu Suria; Yahaya, Yafizah; Mohideen, Fathima Begum Syed; Rashid, Mohd Radzniwan A; Mohamad, Sharifah Najwa Syed; Chamhuri, Nurul Hayati; Noor, Muhammad Tauffik Mohd (Asia-Pacific journal of molecular biology and biotechnology, 2024)
Primary healthcare in Malaysia is pivotal for overall healthcare efficacy, administered by both public and private sectors. However, a significant number of Medical Officers (MOs) and General Practitioners (GPs) lack postgraduate qualifications in general practice, potentially affecting the quality of primary care services. To bridge this gap, the development of a Postgraduate Diploma Program in General Practice (PGDGP) is proposed as an alternative to a master's degree in family medicine. This study aimed to assess their interest and its association with program development through an analysis of the program brochure. A cross-sectional study via an online platform involving 171 respondents was conducted from June to August 2022. The study achieved an 87% response rate, with a majority of respondents being female (63.7%), at M20 level (72%), Malay, and having over five years of work experience. 62% of respondents expressed interest in joining the PGDGP program based on the provided brochure. The significant association involving program fulfillment on the criteria (p = 0.010), proposed syllabus contributes to the program (p=0.004), program covers all the subjects (p=0.000), involvement of multidisciplinary team (p=0.023), Suitable duration (p = 0.000) and mode of the delivery (p=0.005), acceptable fees (p=0.045), program able to enhance skills (p=0.000) and will enhance skills and knowledge (p=0.000) and benefit medical officers (p = 0.004). These findings substantiate the need for further development of the PGDGP program in Malaysia to enhance the quality of primary care efficiently.